Health is wealth : health progrmme - Mackenzie, James; Haldane, William S. ([Scotland : Industrial Health Education Council], 1926)
1926 1926 1920s 16 pages INDUSTRIAL HEALTH EDUCATION COUNCIL. Office-Bearers. President— THE RIGHT HON. LORD SALVESEN, P.C. Vice Presidents— THE RIGHT HON. THE LORD PROVOST OF EDINBURGH. THE RIGHT HON. THE LORD PROVOST OF GLASGOW. THE RIGHT HON. THE LORD PROVOST OF DUNDEE. THE RIGHT HON. THE LORD PROVOST OF ABERDEEN. Chairman— SIR WM. S. HALDANE, W.S. Vice-Chairman— SIR MALCOLM SMITH, K.B.E. Hon. Treasurers— East—MESSRS. GREENHILL & CLAPPERTON, C.A., 31 George Street, Edinburgh. West—MESSRS. MANN, JUDD, GORDON & CO., C.A., 142 St. Vincent Street, Glasgow. Hon. Auditors— MESSRS. W. S. BROWN, MACDONALD & FLEMING, 16 Alva Street, Edinburgh. General Secretary— J. MACKENZIE, 89 Millbrae Road, Langside, Glasgow. 200/B/3/2/C693/1/48